Studi Geseran Spektrum UV Senyawa Asam Barbiturat Pada Plat Al-TLC Si G 60 F254 Akibat Pengaruh Perbedaan pH Pengeluen Untuk Keperluan Uji Konfirmasi - Wirasuta, I. M. A. G.; Indriyaningsih, N. G.; Suaniti, N. M. (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
The UV-spectra-shifting of allobarbital, barbital, butalbital and phenobarbital on AL-TLC-Si gel 60 F254under exposed different pH eluent, drying TLC-plat at 110oC, and then plat placed at room temperature for morethen 17 hours has been carried out. Spectra UV were read by using TLC-Scanner 3 –Camag-Muttenz-Switzerland between 190 and 300 nm. Aim of this research was to study UV-spectra-shifting which can conducterror by confirmation test using in situ UV spectra.There was no significant UV-spectra-shifting of barbiturate on TLC-plate after exposed by mobile phase:10% HCl in methanol (pH=1), chloroform-acetone (80:20, v/v, pH=5), methanol-n-buthanol (60:40, v/v, pH=6),methanol-ammonia (100:1,5, v/v, pH=10) respectively. The significant shifting of UV spectra were obtainedafter TLC-plate exposed by cyclohexane-toluene-diethyl amine (75:15:10, v/v, pH=11) and 0,1 M KOH inmethanol (pH=12), the spectrum shifting was 66% and 23% compared with spectra at pH=1. Drying of the TLCplatesafter exposed by mobile phase conducted no significant UV-spectra shifting, except after exposed bycyclohexane-toluene-diethyl amine (the shifting was 45%). Humidity absorption while placing the TLC-platesat room temperature for more then 17 hours after exposed by strong pH base lead the shifting UV-spectra ofbarbiturate to the weak base or neutral spectra. These shifting UV-spectra should be taken in consideration onconfirmation test of barbiturate based TLC-UV in-situ spectra to reduce error.
Keywords: allobarbital, barbital, butalbital, phenobarbital, AL-TLC-Si gel 60 F254, UV spectrum